2020
DOI: 10.18203/2320-6012.ijrms20200755
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and some demographic factors associated with Toxoplasma gondii infection among female population in Duhok province, Iraq

Abstract: Background: The causative agent of toxoplasmosis is Toxoplasma gondii which is an intracellular protozoan. It has an important role in abortion and congenital diseases in pregnant women, which lead to infant's defectiveness birth when pregnant, are exposed during pregnancy. Toxoplasmosis is one of the most prevalent and most successful parasitic infectious disease worldwide, due to its efficient transmission through the ingestion of tissue cysts in undercooked and infected meat, or the ingestion of oocysts in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Regard to the white blood cells , lymphocytes and granulocytes were increased in IgG positive women compared to negative ones, which agrees with studies Flegr with Stiiz 28 and Leka 29 , this is due to the activation of immune system and immune cells during infection and disagree with a study Hassen et al, 30 . A decrease in red blood cells and hemoglobin had observed in seropositive women which come in accordance with other studies Flegr 28 , Mohamed 31 , and Salih et al, 32 this reduction in hemoglobin in seropositive for anti-Toxoplasma IgG antibodies women may be due to the multiplication of the parasite inside the host body cells and degradation of red blood cells which may cause anemia, that affects directly on the fetus and lead to preterm birth (when delivery occurs before 37 complete weeks of pregnancy) or have a low birth weight baby and postpartum depression.…”
Section: Resultssupporting
confidence: 91%
“…Regard to the white blood cells , lymphocytes and granulocytes were increased in IgG positive women compared to negative ones, which agrees with studies Flegr with Stiiz 28 and Leka 29 , this is due to the activation of immune system and immune cells during infection and disagree with a study Hassen et al, 30 . A decrease in red blood cells and hemoglobin had observed in seropositive women which come in accordance with other studies Flegr 28 , Mohamed 31 , and Salih et al, 32 this reduction in hemoglobin in seropositive for anti-Toxoplasma IgG antibodies women may be due to the multiplication of the parasite inside the host body cells and degradation of red blood cells which may cause anemia, that affects directly on the fetus and lead to preterm birth (when delivery occurs before 37 complete weeks of pregnancy) or have a low birth weight baby and postpartum depression.…”
Section: Resultssupporting
confidence: 91%
“…In Erbil, rates of 37.5% and 34.18% for IgG and 9.13% and 10.86% for IgM, respectively, have been reported [ 21 ]. In Duhok city, Ramadhan and Sarkees have conducted a seroprevalence survey among female undergraduate students [ 22 ], and Salih and colleagues [ 23 ] conducted a study among healthy women and reported rates of 44.4% and 35.61% for IgG and 11.1% and 0.76% for IgM, respectively, while much higher rates for both IgG and IgM at 51.5% and 45%, respectively, have been reported in Kirkuk city [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is somewhat consistent with two previous studies in this city; both studies reported the highest seroprevalence of anti- Toxoplasma IgG and IgM antibodies among those aged 33-45 and 31-35 years, respectively [ 9 , 26 ]. Furthermore, studies from other countries also reported the highest rate of IgG seropositivity among middle ages: 25-32 years in Pakistan [ 27 ], 36-45 years in Duhok [ 23 ], 33-40 years in Nigeria [ 28 ], and 31-40 years in Iran [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…corresponding studies in Duhok City, Iraq conducted by Atroshi and Mero 20 and Ramadhan and Sarkees 21 indicated Toxoplasma seropositivity rates as 27.7% and 44.4%, respectively. Additionally, Salih et al 22 performed another study in Duhokas sessing the seropositivity for Toxoplasma antibodies (36.3%). Additionally, another study 23 demonstrated that the seroprevalence of T. gondii infection in Kirkuk Province, Iraq, was 36.17%.…”
Section: Introductionmentioning
confidence: 99%